Wage diversity in the euro area - an overview of labour cost differentials across industries - Véronique Genre; Daphne Momferatou; Gilles Mourre (European Central Bank (ECB), 2005)
This Paper provides an overview of the magnitude of sectoral wage differentials in the euro area as a whole. Even when adjusting for structural sectoral features such as the skill structure or the proportion of part-timers, average wage levels in services are substantially lower than in manufacturing. The paper also studies how the euro area wage structure compares with that of the United States and the United Kingdom. It discusses some possible determinants of intersectoral wage differentials in the euro area and their likely implications from a policy perspective. A number of worker characteristics (e.g. age, skills, the proportion of temporary or self-employed) are highly correlated with the structure of wage differentials. At the same time, wage differentials are also highly correlated with sector-specific features such as average firm size or capital intensity. Finally, the paper presents some stylised facts on how the euro area wage structure has evolved since the early 1980s.
Keywords: J31; E24; J41; 330; Intersectoral wage differential; wage determination; euro area.; Lohnstruktur; Arbeitskosten; Produktionskosten; Eurozone; EU-Staaten